Neuroticism versus emotionality as mediators of the negative relationship between materialism and well-being - Watson, David C. (Heliyon, 2021)
The purpose of the study was to investigate the relationship between, neuroticism, emotionality well-being and materialism. A series of mediation analyses were conducted with data obtained from a set of questionnaires completed by University students. The results indicated that neuroticism and emotionality were mediators in the well-being-materialism relationship. However, this relationship is dependent upon whether neuroticism or emotionality is measured as the three neuroticism measures utilized were significant mediators whereas the HEXACO emotionality scale was not. A facet-level analysis was conducted with the IPIP-NEO facets of volatility and withdrawal and with the HEXACO facets of sentimentality/dependence and withdrawal. In either case, withdrawal was a significant mediator in the materialism well-being relationship, whereas volatility or sentimentality/dependence was not. The results highlight the differences between neuroticism and HEXACO emotionality and add additional insight into the relationship between materialism and lower well-being. These findings suggest possible methods of decreasing materialistic tendencies and increasing subjective well-being.